THE NEED FOR TRUE COMMUNICATION - Mataboge, E. M. (Scriptura, 1985)
Possibly the greatest tragedy of the division between nations is that for one group God is the god of liberation, while for another He is the god of the status quo. The author argues that for a viable future South Africa needs true reformation. This implies reconciliation between man and man, and between man and God. To bring this about, and heal the divisions in the church, expert help, and better communication should be sought, entailing respectively information about future possibilities, and the ability to listen to other. This will enable the church to be Gods People of the New Covenant, comprising men of all races and languages, and truly become Christ’s presence among men.